(untitled) (Journal of the Management Sciences, 2025)
Human trafficking is a significant global issue, especially in developing nations. This paper explored the efficacy of trauma-focused therapy for human trafficking survivors, addressing the complex psychological and emotional aftermath. Human trafficking subjects victims to severe trauma, including physical violence, sexual exploitation, and psychological manipulation. Trauma-focused therapy is crucial in managing symptoms such as post-traumatic stress disorder (PTSD), anxiety, depression, and dissociative disorders. Drawing on Herman’s (1992) trauma-informed theory, the paper emphasized recognizing trauma’s pervasive impact and providing a safe, supportive environment for recovery. Trauma-informed therapy assists survivors in understanding their experiences, developing coping mechanisms, and reducing the likelihood of re-traumatization. The paper also reviewed barriers to accessing therapy, including stigma, lack of awareness, and structural obstacles like economic instability and legal repercussions. It further examines socio-economic and cultural factors facilitating human trafficking, such as poverty, unemployment, weak legal systems, and cultural practices that devalue women. It also extends to the profound effects on survivors, highlighting the need for comprehensive, culturally competent, and trauma-informed interventions. The paper underscoreed the importance of tailored therapeutic approaches for trafficking survivors, promoting their reintegration and well-being. This paper, therefore, advocated for enhanced awareness, improved access to services, and stronger enforcement of anti-trafficking laws.